The Minister’s intention and the sacrilegious consecration - Astigueta, Damian (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
In this study the canonical terms validity-nullity are considered from the point of view of the theology of the sacraments in relation to the Eucharistic Consecration and thought is given to the case in which the prohibition established in canon 927 is violated, taking very much into account the fact and the meaning of the intention that prevails in the priest that consecrates in those circumstances.
Keywords: sacraments; validity-nullity; Eucharistic Consecration; minister’s intention